Globalization Processes And Human Rights (Zien Journal of Social Sciences and Humanities, 2025)
Globalization processes — including trade, investment flows, technological integration, migration, and cultural exchange — have a multifaceted impact on human rights worldwide. This article examines both the positive and negative aspects of globalization, particularly in relation to labor rights, economic and social rights, cultural and ethnic rights, and migration rights. Based on statistical data and academic research, the legal and practical foundations of globalization processes are analyzed. In conclusion, the paper identifies risk factors of globalization in the context of human rights and offers legal and social measures to mitigate their negative consequences